Indução, duplicação cromossômica e avaliação de marcadores para a detecção de ploidiasem linhagens de milho - Pires, Raquel Maria de Oliveira (2018)
Advances in technologies, aiming the improvement of plants and the production of seeds seeking to optimize issues such as efficiency, time and cost, have been fundamental. One of these technologies is the use of induction of haploid to obtain pure lines, called double-haploid (DH). This technique consists of the crossing of haploid inducing lines with a donor genotype (in vivo induction), identification of possible haploids in seeds or seedling stage, chromosome duplication through the use of antimitotic agents and self-fertilization of DH plants. In order to optimize the steps involved in this process, the objective in the present work was to analyze the capacity of the haploid gymnogenetic inducer line KEMS by means of the haploid induction rate, to validate the efficiency of two chromosome duplication protocols, to verify the capacity of the techniques flow cytometry and SSR molecular markers in the verification of chromosome duplication and to study additional tools for use as indirect markers in the identification of ploidy in order to extrapolate the use of these markers in the identification of haploids in the initial stage of the process of obtaining double-haploids . The haploid inducer line KEMS was used as a male and cross pair with four hybrids (GNS3225, GNS3032, GNS3264 and DKB393). The seeds from this crossing were selected according to the R-Navajo marker and submitted to two different chromosome duplication protocols. In the first protocol, the seeds were germinated on germination paper for 72h at 25oC, and those seedlings considered possible haploids were submitted to treatment with 0.04% colchicine solution and 0.5% dimethyl sulfoxide (DMSO) for 12 hours, and kept in the dark at 20 ° C. In the second protocol, the seeds were sown in trays containing sand and vermiculite. After 10 days, the seedlings considered haploid were immersed in 0.1% colchicine solution, 0.1% dimethylsulfoxide (DMSO) and 0.1% Tween 20, and maintained for 6 hours in the presence of light at room temperature. 22ºC. The plants that survived the chromosome duplication protocols were acclimatized in greenhouse and later transplanted to the field. After selffertilization of the DH0 plants, the DH1 seeds obtained were taken to the field, divided into treatments according to the parental and duplication protocols. At the vegetative stage V4 of the DH1 seedlings, foliar tissue was sampled for the identification of ploidy via flow cytometry, DNA analyzes using microsatellite markers and anatomical character studies. These results were confronted with the morphological characteristics of the DH1 plants developed in the field, evaluated with the use of descriptive tools. The KEMS inducing lineage is capable of inducing haploids. As for the protocols used, there were sign ificant differences in chromosome duplication and in the survival rate of DH0 plants in the field, with protocol 2 being more efficient. However, the use of descriptive tools to evaluate the uniformity of the genotypes submitted to duplication protocols and the segregation of the obtained double haploid materials was not efficient. Flow cytometry techniques and microsatellite markers were efficient in the characterization of duplicate plants and the anatomy showed high accuracy of the studied variables differing individuals through their ploidy.